Decolonial artistic as a potential for recreation of worlds: places to re-exist and re-think oneself (PerCursos, 2021)
This theoretical essay aims to dialogue about art and the artist, based on the contributions of Latin American intellectuals, and promote an analysis of these contributions with the category of the praxis of re-existence. By bringing decolonial reflections into this subject, these authors expand the possibilities of understanding the artist and the art, from Latin America. These intellectuals are Adolfo Alban Achinte, painter and Afro-Colombian researcher, Alfredo Bosi, Brazilian literary historian, and Enrique Dussel, Argentinean philosopher. In the presented reflections about the artistic doing, we recognized its resistance possibilities from the colonial modern power, and the artists recognized as individuals who can contribute to the desired transformations in the decoloniality. We have highlighted some characteristics, such as creative intelligence, critical reflection, relation with time and the capacity of expressing oneself and their environment, considered tools to re-create other logics of being in the world.
Keywords: artists; art; decoloniality; re-existence praxis; creativity